AiiM Lactonase Strongly Reduces Quorum Sensing Controlled Virulence Factors in Clinical Strains of Pseudomonas aeruginosa Isolated From Burned Patients - López-Jácome, Luis Esaú; Garza-Ramos, Georgina; Hernández-Durán, Melissa; Franco-Cendejas, Rafael; Loarca, Daniel; Romero-Martínez, Daniel; Nguyen, Phuong Thi Dong; Maeda, Toshinari; González-Pedrajo, Bertha; Díaz-Guerrero, Miguel; Sánchez-Reyes, Jorge Luis; Díaz-Ramírez, Dánae; et al. (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is an opportunistic bacterium associated with healthcare infections in intensive care units, ventilator-associated pneumonia, surgical site infections and burns. This bacterium causes 75% of death in burned patients, since it can develop a persistent biofilm associated with infections, express several virulence factors and antibiotic-resistance mechanisms. Some of these virulence factors are proteases such as elastase and alkaline protease, or toxic metabolites such as pyocyanin and is one of the few microorganisms able to produce cyanide, which inhibits the cytochrome oxidase of host cells. These virulence factors are controlled by quorum sensing. In this work, 30 P. aeruginosa clinical strains isolated from burned patients from a tertiary hospital in Mexico City were studied. Antibiotic susceptibility tests were done, and virulence factors (elastase, alkaline protease, HCN and pyocyanin) were determined in presence of an N-acylhomoserine lactonase, AiiM able to hydrolyzing a wide range of acyl homoserine lactones. The treatment reduced significantly the activities of elastase and alkaline protease, and the production of pyocyanin and HCN in all producer strains but not the secretion of toxins through the type III secretion system. Our work suggests that AiiM treatment may be an effective therapy to combat P. aeruginosa infection in burn patients.